BRIDGING THE KNOWLEDGE GAP: A COMPARATIVE STUDY OF COUNSELING METHODS FOR ANTENATAL CARE IN PREGNANT WOMEN - Sari, Nanda Rizkita; Andriyanti, Andriyanti; Frety, Endyka Erye (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Introduction: Knowledge of Antenatal Care (ANC) is crucial for the health of pregnant women and their unborn children. Objectives: This study compares the effectiveness of counselling alone versus a combination of counselling and video education on pregnant women's knowledge of integrated ANC at Puskesmas Sekardangan Sidoarjo. Methods: Using a quasi-experimental design with two post-tests only groups, 40 pregnant women were divided into two groups of 20. The control group received counselling, while the intervention group received both counselling and educational videos on ANC. ANC knowledge questionnaires were completed post-intervention and analyzed using the Mann-Whitney test. Results: Results indicated that 65% of the control group had poor knowledge levels, compared to 45% of the intervention group with good knowledge levels. There was a significant increase in knowledge in both groups, with a Z count of -3.525 and a significance value of ρ = 0.000, showing a significant difference between the groups. Conclusion: The study concludes that combining educational videos with counselling is more effective in enhancing pregnant women's knowledge about ANC than counselling alone. Health facilities are recommended to integrate educational videos into ANC counselling programs, with further research needed to explore technology in health education.